Development of 2-D and 3-D culture platforms derived from decellularized nucleus pulposus - Herrera Quijano, Marco A.; Sharma, Nadia; Morissette Martin, Pascal; Séguin, Cheryle A.; Flynn, Lauren E. (Frontiers in Bioengineering and Biotechnology, 2022)
Bioscaffolds derived from the extracellular matrix (ECM) have shown the capacity to promote regeneration by providing tissue-specific biological instructive cues that can enhance cell survival and direct lineage-specific differentiation. This study focused on the development and characterization of two-dimensional (2-D) and three-dimensional (3-D) cell culture platforms incorporating decellularized nucleus pulposus (DNP). First, a detergent-free protocol was developed for decellularizing bovine nucleus pulposus (NP) tissues that was effective at removing cellular content while preserving key ECM constituents including collagens, glycosaminoglycans, and the cell-adhesive glycoproteins laminin and fibronectin. Next, novel 2-D coatings were generated using the DNP or commercially-sourced bovine collagen type I (COL) as a non-tissue-specific control. In addition, cryo-milled DNP or COL particles were incorporated within methacrylated chondroitin sulphate (MCS) hydrogels as a 3-D cell culture platform for exploring the effects of ECM particle composition. Culture studies showed that the 2-D coatings derived from the DNP could support cell attachment and growth, but did not maintain or rescue the phenotype of primary bovine NP cells, which de-differentiated when serially passaged in monolayer culture. Similarly, while bovine NP cells remained highly viable following encapsulation and 14 days of culture within the hydrogel composites, the incorporation of DNP particles within the MCS hydrogels was insufficient to maintain or rescue changes in NP phenotype associated with extended in vitro culture based on gene expression patterns. Overall, DNP produced with our new decellularization protocol was successfully applied to generate both 2-D and 3-D bioscaffolds; however, further studies are required to assess if these platforms can be combined with additional components of the endogenous NP microenvironment to stimulate regeneration or lineage-specific cell differentiation.